A Bibliometric Study of FOMO (Fear of Missing Out) Research and Digital Mental Health (2005–2025) - Judijanto, Loso; Harahap, Taufik (Westscience Press, 2025)
This study performs an extensive bibliometric review of international research on Fear of Missing Out (FoMO) and digital mental health from 2005 to 2025. Data from the Scopus database were utilized to examine 1,226 publications with Bibliometrix (R) and VOSviewer, facilitating the mapping of co-authorship, co-citation, and keyword co-occurrence networks. The findings delineate three primary research domains: FoMO as a psychological construct associated with anxiety and social requirements; FoMO as a precursor to mental health challenges, including depression, loneliness, and internet addiction; and FoMO as a focal point in studies of digital well-being and behavioral control. The United States, Germany, and China are prominent contributors, bolstered by robust international collaboration networks. Temporal and density visualizations indicate a thematic transition from conceptual exploration to preventive and multidisciplinary frameworks that integrate psychology, health, and technology. The research provides actionable insights for the development of digital literacy initiatives and mental health interventions, while underscoring the importance of ethical media utilization. This research provides a comprehensive analysis of the intellectual structure, key contributors, and prospective research goals regarding FoMO and digital mental health, marking one of the initial longitudinal mappings in this field.